Smartwatch digital phenotypes predict positive and negative symptom variation in a longitudinal monitoring study of patients with psychotic disorders - Kalisperakis, Emmanouil; Karantinos, Thomas; Lazaridi, Marina; Garyfalli, Vasiliki; Filntisis, Panagiotis P.; Zlatintsi, Athanasia; Efthymiou, Niki; Mantas, Asimakis; Mantonakis, Leonidas; Mougiakos, Theodoros; Maglogiannis, Ilias; Tsanakas, Panayotis; et al. (Frontiers in Psychiatry, 2023)
Monitoring biometric data using smartwatches (digital phenotypes) provides a novel approach for quantifying behavior in patients with psychiatric disorders. We tested whether such digital phenotypes predict changes in psychopathology of patients with psychotic disorders. We continuously monitored digital phenotypes from 35 patients (20 with schizophrenia and 15 with bipolar spectrum disorders) using a commercial smartwatch for a period of up to 14 months. These included 5-minute measures of fine motor activity from an accelerometer (FMA), average Heart Rate (HRA) and heart rate variability (HRV) from a plethysmography-based sensor, gross motor activity (GMA) measured as number of total steps per day and sleep/wake ratio (SWR). A self-reporting questionnaire (IPAQ) assessed weekly physical activity. After pooling phenotype data, their monthly mean and variance was correlated within each patient with psychopathology scores (PANSS) assessed monthly. Our results indicate that increased HRA during wakefulness and sleep correlated with increases in positive psychopathology. Besides, decreased HRV and increase in its monthly variance correlated with increases in negative psychopathology. Self-reported physical activity did not correlate with changes in psychopathology. These effects were independent from a series of demographic and clinical (including diagnosis) variables as well as changes in antipsychotic medication dose. Our findings suggest that distinct digital phenotypes derived passively from a smartwatch can predict variations in positive and negative dimensions of psychopathology of patients with psychotic disorders, over time, providing ground evidence for their potential clinical use.